A Novel Hybrid T-Type Three-Level Inverter Based on SVPWM for PV Application. (3rd June 2018) - Tuluhong, Ayiguzhali; Wang, Weiqing; Li, Yongdong; Xu, Lie
Abstract : We describe several, recently reported, new topologies and compare them with each other, in order to find out the optimal multilevel grid-connected inverter topology. Then, we classify these topologies according to the basic unit which predecessors proposed. Eventually, we propose the hybrid T-type inverter topology structure, which is composed of two best basic units. This structure takes full advantage of the two components, to reduce the harmonic content and the power loss of the converter and improve the conversion efficiency of the system. At the same time, the space vector pulse width modulation (SVPWM) method is used to simulate the proposed topology in the MATLAB/SIMULINK platform, while the loss of each semiconductor switch is calculated using MELCOSIM software. The results show that the proposed structure is superior to the most widely used topology, i.e., the diode clamped and the T-type three-level circuits.